2022
DOI: 10.3389/fped.2022.919403
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-Associated Infection Prevention Interventions for Neonates in Resource-Limited Settings

Abstract: Healthcare-associated infections (HAIs) and antimicrobial-resistant (AMR) infections are leading causes of neonatal morbidity and mortality, contributing to an extended hospital stay and increased healthcare costs. Although the burden and impact of HAI/AMR in resource-limited neonatal units are substantial, there are few HAI/AMR prevention studies in these settings. We reviewed the mechanism of action and evidence supporting HAI/AMR prevention interventions, including care bundles, for hospitalized neonates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 137 publications
1
9
0
Order By: Relevance
“…Compared to other WHO regions, the Africa region has the lowest HHSAF scores (mean 281, SD 127), possibly owing to poor healthcare infrastructure, lack of infection prevention resources, and a limited knowledge of HH implementation and sustainability [ 55 ]. Our post-intervention neonatal unit HHSAF score of 262 (intermediate level) is in keeping with scores reported from other LMIC settings with median HHSAF survey scores ranging from 233 in low-income countries to 395 in high-income countries [ 53 , 56 ]. The disparity between the HHSAF and the HH compliance and other related variables highlights the fact that institutional progress and commitment to HH does not always achieve behavior change at the level of the individual.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Compared to other WHO regions, the Africa region has the lowest HHSAF scores (mean 281, SD 127), possibly owing to poor healthcare infrastructure, lack of infection prevention resources, and a limited knowledge of HH implementation and sustainability [ 55 ]. Our post-intervention neonatal unit HHSAF score of 262 (intermediate level) is in keeping with scores reported from other LMIC settings with median HHSAF survey scores ranging from 233 in low-income countries to 395 in high-income countries [ 53 , 56 ]. The disparity between the HHSAF and the HH compliance and other related variables highlights the fact that institutional progress and commitment to HH does not always achieve behavior change at the level of the individual.…”
Section: Discussionsupporting
confidence: 83%
“…High neonatal bed occupancy rates (85–91%) and suboptimal staff-to-patient ratios contributed to the challenges in ensuring compliance with HH recommendations and other infection best practices. This highlights the need to implement multimodal infection prevention strategies in LMIC neonatal units, where the causal pathway from colonisation to infection is particularly complex [ 56 ]. The study was not designed to explain differences in the effectiveness of the intervention in healthcare workers versus mothers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we may not have captured the medical staff quality, including hygiene and insight about nosocomial infection and antibiotic resistance that is related to resistant pathogen infection in other general studies. 17,18 In conclusion, invasive procedures, central access insertion, and the provision of parenteral nutrition have a significant correlation with the…”
Section: Discussionmentioning
confidence: 98%
“…Smit et al (2018) demonstrated that ESBL- K. pneumoniae were transmitted between humans and 22% of neonate infections were due to environmental source (19). Furthermore, Dramowski et al (2022) emphasized the importance of WASH and IPC in the early and heavy bacterial colonization of neonates in resource-limited settings and recommended sustained neonatal IPC and surveillance programs in neonatal units in these settings (20). Healthcare workers colonized with MDR-ESBL isolates could thus contribute to the ongoing transmission of resistant bacteria to neonates where they could subsequently cause life-threatening neonatal infections such as sepsis, meningitidis or pneumoniae.…”
Section: Discussionmentioning
confidence: 99%